Robust Approaches for the Production of Active Ingredient and Drug Product for Human Phage Therapy - Mutti, Michele; Corsini, Lorenzo (Frontiers in Microbiology, 2019)
To be successful, academic and commercial efforts to reintroduce phage therapy must ensure that only safe and efficacious products are used to treat patients. This raises a number of manufacturing, formulation and delivery challenges. Since phages are biologics, robust manufacturing processes will be crucial to avoid unwanted variability in each step of the process. The quality standards themselves need to be developed, as patients are currently being treated with phages produced under quality standards ranging from cGMP for clinical trials in EMA and FDA regulated environments to no standards at all in some last resort treatments. In this short review, we will systematically review the literature covering technical issues and approaches to increase robustness at every step of the production process: the identity of the phage and bacterial production strains, the fermentation process and purification, the formulation of the drug product, the quality controls and the documentation standards themselves. We conclude that it is possible to control cost at the same time – which is critical to re-introduce phage therapy to western medicine.